A new sesarmid crab of the genus Karstarma (Crustacea: Decapoda: Brachyura) associated with limestone formations in East Java, Indonesia - Wowor, Daisy; Ng, Peter K. L. (Zootaxa, 2018)
A new stygobitic sesarmid crab species is described from underground freshwater cave streams in the southern Malang karst range on the south coast of East Java Province, Indonesia. Karstarma malang n. sp. is morphologically most similar to K. jacobsoni (Ihle, 1912) from an underground river cave system in the southern coast of the Special Region of Yogyakarta Province in central Java, but differs in having a relatively larger cornea, less swollen ocular peduncle which lacks a ridge along the median part, proportionately shorter ambulatory legs and a more slender male first gonopod. This paper increases the number of the species of Karstarma Davie & Ng, 2007, to 16; the new species being the eighth of the genus from Indonesia. It is also the third species which has a distinctly reduced cornea.